Inflammatory skin disorders - Plaza, Jose A. , 1968-; Prieto, Victor G. (Demos Surgical Pathology Guides, 2012)
The Demos Surgical Pathology Guides series presents in summary and visual form thebasic knowledge base that every practicing pathologist needs every working day. Seriesvolumes cover the major specialty areas of surgical pathology, and coverage emphasizesthe key entities and diagnoses that pathologists will see in practice, and that they mustknow whether in training or practice. The emphasis is on the basic morphology with newertechniques represented where they are frequently used. The series provides a handy summaryand quick reference that any pathology resident or fellow will find useful. Exp